Si Rukat Nakan dalam Masyarakat Karo - Raharja Sembiring; Dina Datu Paonganan; Rut Debora Butar-butar (Universitas Negeri Medan, 2021)
This article aims to describe the relations of equality and respect for men and women in the Karo cultural frame. The relationship between the two, where adat (culture) is the main reference often has bad-faced implications for the Karo patriarchy. Patriarch Karo is often claimed not to have a space of equality and respect for women. The problem will be focused on the use of idioms attached to Karo women. One idiom that is very attached to Karo women is rukat nakan. Idiom the rukat nakan describes the domestic duties of women, namely arranging accommodation and household logistics. With regard to the relationship between men and women, feminists claim the rukat nakan idiom is a form of condescension toward women, even an attempt to domesticate Karo patriarchal role of women. On the other hand, this idiom is also often referred to to validate the wife's subordination to her husband. The results of the research through interviews, literary research and analysis of Karo song poems, the idioms of rukat nakan are an illustration of the appreciation of the domestic role of women. Si rukat nakan is a domestic assignment which describes a very private relationship between husband and wife. The term “si rukat nakan” is not to denigrate or domesticate women, but it shows respect for women's roles.